2020
DOI: 10.5935/2447-0228.20200012
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Linear Programming Model to Maximize Profit With Minimized Lead Time of a Composite Textile Mill

Abstract: In the competitive market of apparel manufacturing, lead time for production plays a significant role in the delivery of the produces impacting the entire supply chain. Nowadays, composite manufacturers are leaning towards delivering within the shortest possible time to retain customers in this competitive market. To meet this challenge, proper production planning either using the correct method or the appropriate tools is a prerequisite condition; otherwise, mills will inevitably suffer losses or fail to drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The result indicated that the bakery should generate and market more small loaves and big loaves to maximize the profit. Ghosh et al [27] developed a linear programming model to reduce the complexity of a Composite Textile Industry's scheduling problem in pursuit of maximizing profit. The model is developed considering process segmentation, utilization of machines, and other resources, concerning lead time.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The result indicated that the bakery should generate and market more small loaves and big loaves to maximize the profit. Ghosh et al [27] developed a linear programming model to reduce the complexity of a Composite Textile Industry's scheduling problem in pursuit of maximizing profit. The model is developed considering process segmentation, utilization of machines, and other resources, concerning lead time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Four different leadtime components are derived, and Microsoft Excel solver is used in solving the model. Ghosh et al [27] found that the maximum profit is $5164, and the Composite Textile Industry will gain this maximum profit if the project is completed within 31 days.…”
Section: Literature Reviewmentioning
confidence: 99%